Prevalence of dental caries in children with congenital heart disease - Steffen Koerdt; Julia Hartz; Stefan Hollatz; Max Heiland; Norbert Neckel; Peter Ewert; Renate Oberhoffer; Herbert Deppe (BMC, 2022)
Abstract Background Congenital heart defects (CHD) affect about 8 out of 1000 births worldwide. Most of the patients reach adulthood and are exposed to an increased risk of endocarditis. Since bacteria already enter the bloodstream during everyday activities, oral hygiene is given special importance in the prevention of endocarditis. Methods In this study 81 boys (55.1%) and 66 (44.9%) girls with CHD received a dental exam and additionally an assessment using the DIAGNOdent® pen. This study group consisting of patients with CHD was matched with a healthy epidemiological control group in Germany. Results Eighty-one boys (55.1%) and 66 (44.9%) girls were examined. The mean age was 11 ± 4 years. 38.8% showed at least one untreated carious lesions. 37.4% had a dmft/DMFT ≥2 and thus represented a group with an increased caries risk. The dmft value was 2.12 ± 1.25 in the age group 3-6 year olds. In the group of the 7-12 year old patients the DMFT/dmft was 2.06 ± 2.27, whereas DMFT in 13-17 year olds was at 2.12 ± 1.58. However, children and adolescents with CHD had a higher DMF index than healthy children in the same age group. Conclusions The present study reveals that more than one third of those examined have a dental condition in need of rehabilitation. In future, close interdisciplinary cooperation between pediatric cardiologists and dentists should ensure regular dental check-ups.